Development of mathematics learning tools through scientific approach with problem based learning (PBL) settings to improve motivation and learning achievement - Ni Luh Sintya Dewi; Gede Suweken; I Gusti Putu Sudiarta (Universitas Pendidikan Ganesha, 2019)
This research aimed at obtaining a scientific learning tool in the scientific approach with a valid, practical and effective problem based learning (PBL) setting. This development research was carried out according to Plomp & Nieveen (2010), i.e. (1) initial phase, (2) prototype phase, and (3) assessment phase (semi-summative evaluation). The learning tools consisted of student books and teacher manuals. This research was carried out at SMP Negeri 4 Mengwi. Learning device quality data was collected with validation sheets, learning device implementation sheets, student response questionnaires and teacher responses, motivation questionnaires and mathematics learning achievement tests. The characteristics of student books are (1) learning begins with real problems in everyday life that related to the material being studied; (2) students are given the opportunity to ask questions from the observations that have been done and answered by their colleagues; (3) discuss and seek solutions from the problem of